Emotion, Reason and Action in Kant - Borges, Maria de Lourdes (Bloomsbury Academic, 2019)
This book explores how, in Kant's world view, our actions are informed, contextualized and dependent on the tension between emotion and reason. Arguing that affects and passions are illnesses of the mind, because both hinder the sovereignty of reason, Borges demonstrates Kant's recognition of the malleability of reason. To this end, the book explores the full range of negative and positive emotions in Kant's work, including self-control, compassion, sympathy, as well as anger. Kant's argument on the gendered nature of emotion, that women's innate morality disciplined men's tendency to behave in immoral ways, is also discussed. Finally, Borges shows how Kant's theory of emotion includes both physiological and cognitive aspects. Emotion, Reason and Action in Kant is an important new contribution to Kant Studies, suitable for students of Kant, ethics, and moral psychology.